PRINSIP-PRINSIP DASAR EVALUASI DAN IMPLIKASI DALAM MENILAI INSTRUKSI IMAN ISLAM DI LEMBAGA PENDIDIKAN - Upiyani, Upiyani; Cahyawati, Ita; Supendi, Sinta Silvia; Nugraha, Enung; Hidayat, Wahyu (PAI RAFAH, 2024)
The study uses qualitative research strategies and uses literature review methodologies. Evaluation includes measurement and assessment, as demonstrated by the results of the discussion. Evaluation has a significant and strategic role in the field of learning, as it is covered in the framework of learning evaluation. The aim is to evaluate the effectiveness and efficiency of the education system. This field of study includes curriculum evaluation, evaluation of the learning process, and examination of learning outcomes. The concept of evaluation usually includes the following elements: continuity, comprehensive, fair, objective, collaborative, and practical. The values discussed include integrity, coherence, pedagogy, and accountability. Assessment of Islamic education in educational institutions must be done in a sustainable, comprehensive, and integrated manner, with an implicit understanding. Therefore, it is essential for Islamic Religious Education instructors to have the ability to evaluate student progress, covering the cognitive, affective, and psychomotor domain dimensions.